PREVALENCE OF TOXOCARA CANIS INFECTION IN DOGS AND ITS EFFECTS ON VARIOUS BLOOD PARAMETERS IN LAHORE (PAKISTAN) - M. A. Chattha; A. Aslam; Z. U. Rehman; J. A. Khan; M. Avais (Journal of Animal and Plant Sciences, 2009)
The present study was conducted to find out the prevalence of Toxocara canis in Lahore, Pakistan and its effect on hemogram in dogs. For this purpose a total of 200 fecal and blood samples from dogs (n=100 stray dogs, n=100 pet dogs) were collected and examined. The results revealed the prevalence of Toxocara canis as 49% and 30% in stray and pet dogs, respectively. A significant decrease was recorded in hemoglobin level, packed cell volume and total erythrocyte count where as values were on higher side for total leukocytes count and erythrocyte sedimentation rate in dogs infected with Toxocara canis.
Keywords: Toxocara canis; hemogram; Lahore; erythrocytes; stray dogs